First aid education in schools - Al Hashil, Hashil Hassan; Al Hashil, Hassan Salem; Al Alhareth, Musalli Naji; Al Mansour, Hussein Yahya; Al Hutayla, Yaseen Mesfer (Journal of medical and pharmaceutical sciences, 2024)
Background: First aid training is very important as it proves to be an essential skill in helping someone in an emergency situation and saving lives. One of the benefits of incorporating first aid training in schools is that students get an opportunity to learn critical skills that may save a life. Objectives: This research was carried out to evaluate the effectiveness of school-based first aid interventions in mitigating injuries, improving psychological health, and enhancing school safety. This paper also, assessed the current state of first aid education, exploring the benefits of early intervention, identifying challenges, and opportunities for interdisciplinary collaboration in implementing first aid programs. Methodology: An exhaustive survey of relevant literature was conducted including but not limited to periodicals, research papers, policy statements and government reports. Results: This study highlights the effectiveness of school-based first aid programs in enhancing school safety, reducing injury severity, and improving psychological well-being among students and staff. Despite these benefits, challenges like resource limitations and logistical barriers restrict widespread implementation. Effective collaboration among schools, community organizations, and healthcare providers is crucial to overcoming these obstacles and ensuring program success. Conclusion: The study concluded that first aid training in schools enhances safety, reduces injury severity, and improves psychological well-being. Collaboration between schools and health organizations is essential to overcome challenges and ensure successful implementation.
Keywords: First aid; Injury prevention; Emergency response; CPR